The prevalence of psychological stress and its associated factors among secondary school teachers in Samarahan and Asajaya district - Mardhiyyah A; Ayu Akida Abdul Rashid (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
A wide range of occupations have been associated with psychological stress, and the teaching profession has been considered as one of the most stressful jobs. This study aimed to determine the prevalence of psychological stress and its associated factors among secondary school teachers. A cross-sectional study was conducted among secondary school teachers in Samarahan and Asajaya districts using selfadministered questionnaires. The status of psychological stress was measured using the Malay version of DASS-21. The Teachers Stress Inventory was adapted to identify the psychosocial factors. The overall prevalence of psychological stress from this study was 19.5%. Out of 241 teachers, 9.1% had mild stress, 7.1% had moderate stress, and 3.3% had severe to very severe stress. The prevalence of psychological stress was significant among younger teachers, single, divorced or widowed, and those with the least household income. Among occupational factors, only the number of years of teaching experience has a significant relationship with psychological stress. The logistic regression analysis identified four significant elements associated with psychological stress, notably household income, anxiety, depression and time management. As a conclusion, the burden of psychological stress among school teachers can be associated with either individual factors or work-related factors. The responsibility in managing mental health among teachers does not only lie with the individual but at every level in the organisation. The surveillance systems for early detection of psychological stress can be implemented at the school level.